Effect of Different Doses of Acetylsalicylic Acid on the Antithrombotic Activity of Clopidogrel in a Mouse Arterial Thrombosis Model. Issue 10 (October 2018) - Ni, Ran; Vaezzadeh, Nima; Zhou, Ji; Weitz, Jeffrey I.; Cattaneo, Marco; Gross, Peter L.
Abstract : Objective—: Dual-antiplatelet therapy with acetylsalicylic acid and a P2Y12 antagonist, such as clopidogrel, is the standard of care for acute coronary syndromes. However, the drugs have divergent effects on the formation of cAMP, an inhibitory second messenger. Thus, by inhibiting the synthesis of prostacyclin, acetylsalicylic acid reduces cAMP formation, whereas clopidogrel potentiates it. Therefore, with higher doses of acetylsalicylic acid, the potentiation of cAMP production by clopidogrel may be attenuated, which could limit the antithrombotic potential of the drug combination. The purpose of this study was to examine this possibility in vivo. Approach and Results—: Mice were given oral acetylsalicylic acid at varying doses, oral clopidogrel (5 mg/kg body weight), or both. At doses of 0.15 and 0.6 mg/kg, acetylsalicylic acid inhibited arachidonic acid–induced platelet aggregation, but only 0.6 mg/kg acetylsalicylic acid, or higher, decreased the plasma levels of 6-keto-prostaglandin-F1α, the stable metabolite of prostacyclin. When given with clopidogrel, laser injury–induced arterial thrombi were significantly larger with the 0.6 mg/kg dose of acetylsalicylic acid than with the 0.15 mg/kg dose. Thrombi in mice treated with clopidogrel and the 0.15 mg/kg dose of acetylsalicylic acid were smaller than in mice treated with clopidogrel alone, suggesting that acetylsalicylic acid can add to the antithrombotic effect of clopidogrel but that higher doses of acetylsalicylic acid blunt the antithrombotic effect of clopidogrel. Conclusions—: These findings support the use of lower, prostacyclin-preserving, doses of acetylsalicylic acid in conjunction with clopidogrel. Abstract : Supplemental Digital Content is available in the text.